Manfaat Penggunaan Metode Mind Mapping pada Pembelajaran IPA Bagi Siswa Sekolah Dasar - Syarifa, Saila Rizqa; Dhiya, Fariha Aqbil; Rahmaniah, Rihhadatul (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Implementing the right methods in learning can improve innovative learning systems and adapt to the current condition of students. In addition, it can provide motivation to students to become better, more active in learning, create a pleasant atmosphere, and have a real impact on the results of teaching telrselbult students. This article aims to explore the use of mind mapping in science learning for elementary school students. Mind mapping is a cell or meltodel to synchronize the right brain and left brain in receiving new information. Mind mapping is the most relative and efficient way to take notes, using mind mapping, it is hoped that students will become more relative, self-confident, and able to master learning more efficiently. This research is qualitative research with literature study. The method of obtaining data is by analyzing sources and combining from various other reference sources, such as journals, research, and books conducted by previous researchers. The analysis technique used in this research is Content Analysis (content analysis). Through this mind mapping, students are expected to be able to express their knowledge, intelligence, and imagination thinking with the aim of turning students into memorization that is comfortable for them